Types of Personality Profiles of Men and Women Suffering from Paranoid Schizophrenia - AymedovК.; Morvanyuk, G. (Psychiatry, Neurology and Medical Psychology, 2016)
The article deals with individual psychological characteristics of men and womens offering from paranoid schizophrenia. We showed personality profiles identified in the analysis of the results of psycho-diagnostic evaluation of patients with paranoid schizophrenia. Мost patients were psychotic, neurotic or hypоthymic profile option. The findings should be considered in the organization of complex therapeutic interventions for patients with paranoid schizophrenia.